Factors influencing the intention to adopt green supply chain initiatives in manufacturing firms based on Theory of Planned Behavior (TPB) - Jo Ying, Lee (2014)
Nowadays, manufacturing ﬁrms have exerted huge impacts toward the degradation of the environment. It’s essential for the ﬁrms to implement green practices in order to conserve the Mother Nature. However, the intention of the ﬁrms to practice green supply chain initiatives (GSCI) remained ambiguous. Hence, this research was carried out to analyze the factors inﬂuencing the intention to adopt GSCI in manufacturing ﬁrms. Theory of Planned Behavior (TPB) model with three attributes, namely attitude (ATT), subjective norm (SN) and perceived behavioral control (PBC) was applied as a framework to predict the intention to adopt green purchasing (INTGP), eco-design (INTED) and reverse logistics (INTRL). The data was successfully collected from 50 respondents at Electronics & Electrical (E&E) manufacturing ﬁrms in Penang. Purchasing and Operation & Production manager’s intention were treated as the proxy to ascertain the ﬁrm’s behavioral intention. Data was analyzed by using the IBM Statistical Package for Social Science Software (SPSS 22). Multiple regressions were carried out for hypotheses testing. TPB attributes were able to explain 46.5% of variance in INTGP, 9.8% of variance in INTED and 23% of variance in INTRL. Consequently, PBC was the only signiﬁcant predictor of INTGP and INTRL. The results provide practical implications for researcher, managers, as well as practitioners to implement strategies for behavioral intervention and designation of policy to inﬂuence ﬁrm’s intention to practice GSCI